Family Enterprises and Minority Shareholders: Benefits and Risks in Corporate Governance - Li, Jialong (International Journal of Global Economics and Management, 2024)
This essay mainly studies the benefits of minority shareholders in family businesses. Through the Secondary research method to investigate the relevant data of countries worldwide, it is found that family businesses dominate the global business and make significant contributions to employment and GDP growth. Moreover, family enterprises attach importance to brand inheritance and the long-term development of the company. Their good brand image and endurance in difficulties have increased the overall revenue of the company, thus benefiting minority shareholders to a certain extent. Nevertheless, this essay points out that there is a unique "agency issue" in family enterprises and demonstrates that this issue will damage the interests of minority shareholders through the case of Samsung. Furthermore, this essay finds that family infighting is more likely to occur in older family businesses, which brings a new research dimension to family business governance.